Research of the possibilities of creating and supporting inclusive tourist services - Захаров Д.В.; Купач, Тетяна Геннадіївна (Київський національний університет імені Тараса Шевченка, 2024)
The article discusses the topic of development of inclusive tourism and the possibility of introducing inclusive tourist services. The importance of ensuring the availability of tourist services for all categories of the population is analyzed. The main challenges faced by the industry during the implementation of inclusive solutions are identified, and the prospects for the further development of this segment of tourism are outlined. The analysis of scientific literature on inclusive tourism showed that there is currently no generally accepted definition for this type of tourism in Ukraine. However, inclusive tourism is an important aspect of tourism development, especially for people with disabilities. This type of tourism is developing all over the world, and countries are actively adapting their tourism infrastructure to ensure a comfortable vacation for everyone. However, various problems of the development of inclusive tourism in Ukraine indicate the need for increased and comprehensive attention from the state and society. Despite the availability of both theoretical and scientific-practical studies, the issues of tourism development for people with disabilities in Ukraine remain insufficiently studied.

У статті розглянуто тему розвитку інклюзивного туризму та можливості впровадження інклюзивних туристичних сервісів. Проаналізовано важливість забезпечення доступності туристичних послуг для всіх категорій населення. Визначено основні виклики, з якими стикається індустрія під час впровадження інклюзивних рішень, і окреслено перспективи подальшого розвитку цього сегменту туризму. Аналіз наукової літератури щодо інклюзивного туризму показав, що в Україні нині не існує загальноприйнятого визначення для даного виду туризму. Тим не менше, інклюзивний туризм – це важливий аспект розвитку туристичної галузі, особливо для людей з обмеженими можливостями. Цей вид туризму розвивається у всьому світі, і країни активно адаптують свою туристичну інфраструктуру для забезпечення комфортного відпочинку для всіх. Втім, різноманітні проблеми розвитку інклюзивного туризму в Україні свідчать про необхідність посиленої та комплексної уваги з боку держави та суспільства. Попри наявність як теоретичних, так і науково-практичних досліджень, питання розвитку туризму для людей з інвалідністю в Україні залишаються недостатньо вивченими.
Дослідження можливостей створення та підтримки інклюзивних туристичних сервісів
Keywords: інклюзивний туризм; інклюзивні туристичні сервіси; inclusive tourism; inclusive tourist services